2013
DOI: 10.1007/s11882-013-0389-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tobacco Smoke Exposure in Childhood on Atopic Diseases

Abstract: Although the smoking prevalence in the United States continues to decline since the Surgeon General’s first report in 1964, certain vulnerable populations continue to be disproportionately affected by the adverse consequences of tobacco smoke exposure. Children are particularly vulnerable to exposure and are likely to suffer from both short- and long-term adverse consequences after early life tobacco smoke exposure. An overwhelming amount of evidence supports an association between asthma development and tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
(46 reference statements)
1
21
0
2
Order By: Relevance
“…In line to this, nicotine has been shown to reduce atopic disorders such as asthma and preeclampsia [30]. Mechanism of action in these cases may be, nicotine interfering with the inflammationrelated disease process, as nicotine has vaso-constrictive effects [31].…”
Section: Discussionmentioning
confidence: 95%
“…In line to this, nicotine has been shown to reduce atopic disorders such as asthma and preeclampsia [30]. Mechanism of action in these cases may be, nicotine interfering with the inflammationrelated disease process, as nicotine has vaso-constrictive effects [31].…”
Section: Discussionmentioning
confidence: 95%
“…Another study (29) reported that higher expression of CD14 and TLR genes was related to protective factors (farming environments, endotoxin, extracellular polysaccharides) against the development of asthma and wheezing in children. Air pollutants such as those contained in environmental tobacco smoke present a considerable health problem to the general population, including non-smokers (16,(30)(31)(32). Some studies suggest that active and passive smoking present the risk of IgE sensitisation and atopic conditions, atopic rhinitis and dermatitis in particular (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants such as those contained in environmental tobacco smoke present a considerable health problem to the general population, including non-smokers (16,(30)(31)(32). Some studies suggest that active and passive smoking present the risk of IgE sensitisation and atopic conditions, atopic rhinitis and dermatitis in particular (32,33). Our study however found no correlation between passive smoking and elevated IgE in either atopic or non-atopic adolescents, but in atopics passive smoking showed a borderline significant effect on sCD14 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The cytomorphological and functional integrity of these membranesis animportant element of the first line of defense against the effectsof unfavorable environmental factors associated with exposure to tobacco smoke [14][15][16]. Tobacco smoke can trigger allergic sensitization that directly affects immunoglobulin-E at the cellular level and can increase the permeability of the epithelium of the airways, further reducing its function as a protective barrier [17][18][19].…”
Section: Introductionmentioning
confidence: 99%